The Use of Digital Finance Applications, Competitiveness, and Green Economy on Village Development - I Gusti Ayu Purnamawati; Kadek Rai Suwena; Komang Krisna Heryanda (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2023)
Conducting an analysis of the role of digital financial applications, competitiveness, and a green economy for village development innovation is the aim of this research. The research uses an explanatory approach with research locations in the Province of Bali. Primary data was collected using a questionnaire with a Likert scale of 1 to 5. Respondents included 165 owners of micro, small, and medium enterprises and were determined purposively which were then analyzed using Structural Equation Modeling. The results of the study provide evidence of a positive and significant relationship between the variables of implementing digital finance, competitiveness, and the development of village development innovations. The application of the green economy has not fully influenced village development innovations. In the future, it is expected to provide optimal opportunities to encourage a low-carbon economy. The digital village has contributed to improving the village government service system, community, and empowerment based on information technology.